2017
DOI: 10.1055/s-0037-1598201
|View full text |Cite
|
Sign up to set email alerts
|

National Breast Reconstruction Utilization in the Setting of Postmastectomy Radiotherapy

Abstract: Background Immediate breast reconstruction (IBR) is often deferred, when post-mastectomy radiotherapy (PMRT) is anticipated, due to high complication rates. Nonetheless, because of robust data supporting improved health related quality of life associated with reconstruction, physicians and patients may be more accepting of trade-offs. The current study explores national trends of IBR utilization rates and methods in the setting of PMRT, using the National Cancer Data Base (NCDB). The study hypothesis is that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…The role of IBR in the use of PMRT has been explored previously using the NCDB. Recent data demonstrate that rates of PMRT in this group of reconstructed patients increased from 13% in 2004 to 33% in 2013 . Conversely, a Surveillance, Epidemiology, and End Results study indicated that the number of women who require PMRT and opt for IBR has increased over time between 2000 and 2010 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of IBR in the use of PMRT has been explored previously using the NCDB. Recent data demonstrate that rates of PMRT in this group of reconstructed patients increased from 13% in 2004 to 33% in 2013 . Conversely, a Surveillance, Epidemiology, and End Results study indicated that the number of women who require PMRT and opt for IBR has increased over time between 2000 and 2010 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data demonstrate that rates of PMRT in this group of reconstructed patients increased from 13% in 2004 to 33% in 2013. 16 Conversely, a Surveillance, Epidemiology, and End Results study indicated that the number of women who require PMRT and opt for IBR has increased over time between 2000 and 2010. 17 Taken together, these data suggesting that the use of PMRT and IBR are not mutually exclusive, although it is difficult to ascertain whether the indication for PMRT affects IBR or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple advocacy groups and campaigns through social media have also increased the national presence of breast disease, and have heightened awareness about the improved HR-QoL benefits associated with breast reconstruction. Jointly, these factors contributed to the upsurge in the proportion of women obtaining breast reconstruction with rates as low as 8% in 1995 to recently published rates of about 41% in 2013 based on an NCDB analysis [39, 40]. The latest rate of IBR for 2014 using the American College of Surgeons National Surgical Quality Improvement Program data was reported to be as high as 54% of invasive cancer cases and 63% of ductal carcinoma in situ cases [41].…”
Section: The Rate Of Breast Reconstructionmentioning
confidence: 99%
“…Interestingly, the annual increase in the rates of reconstruction among radiated patients was steeper than that in non-radiated ones for both implants (15% versus 11%), as well as flap-based reconstructions (8% versus 6%). By 2008, implant-based reconstruction surpassed ABR as the more common method of reconstruction in the setting of PMRT [39]. …”
Section: Radiotherapy and Immediate Breast Reconstructionmentioning
confidence: 99%
“…Breast reconstruction may be undertaken as an immediate procedure (at the same session as the mastectomy itself), which allows for skin‐ or nipple‐sparing options, or as a delayed procedure (delayed breast reconstruction, DBR). Immediate breast reconstruction (IBR) is an increasingly common reconstructive option, even in the setting of postmastectomy radiotherapy. Despite the negative impact of postmastectomy radiotherapy on surgical and patient‐reported outcomes after IBR, this option is widely accepted today, possibly due to the use of autologous techniques, different radiation strategies in the USA, or the increased use of meshes and matrices, with the implant placed in the prepectoral or subpectoral space.…”
Section: Introductionmentioning
confidence: 99%